Antipsychotic drugs and sudden cardiac death: A literature review of the challenges in the prediction, management, and future steps. (November 2019) - Zhu, Jingjing; Hou, Weihong; Xu, Yong; Ji, Feng; Wang, Guowei; Chen, Ce; Lin, Chongguang; Lin, Xiodong; Li, Jie; Zhuo, Chuanjun; Shao, Mingjng
Highlights: Connections are established between antipsychotics and sudden cardiac death (SCD). Prediction and management of SCD in users of antipsychotics are challenging. The risk for SCD in users of antipsychotics can be assessed. New wearable devices may detect early signs of antipsychotic-related SCD. Abstract: Sudden cardiac death (SCD) is relatively uncommon, yet it is a deadly consequence of some antipsychotic medications in patients with psychiatric disorders. The widespread concerns about the adverse cardiac effects associated with antipsychotics and their unpredictable nature have led to a restriction on the use of some antipsychotic medications. Recent progress has been made in the identification of important genetic factors that may contribute to the adverse complication of antipsychotic drugs, suggesting that high-risk individuals can be identified prior to initiating therapy. In addition, some high-tech smart wearable medical devices have recently been developed, allowing users to record and analyze the electrocardiogram (ECG) in couple with artificial intelligence (AI) technologies, and notifying of irregular heart rhythms or arrhythmias, a medical condition well documented in most SCD cases. In this literature review, we summarize recent advances in understanding the link between SCD and antipsychotic drug usage, as well as in utilizing wearable medical devices for monitoring of cardiac arrhythmias. New strategies for improving the care of patients receiving antipsychotic medications are proposed. As it is now possible to evaluate the risk of SCD in patients on antipsychotic medications, preventative measures and close monitoring may be used to detect the early signs of adverse cardiac events and SCD.